Beyond the wall - Leverage, Henry, 1885-1931 (Salt Lake City, UT : Project Gutenberg, 2022)
"Beyond the Wall" by Henry Leverage is a thrilling novel likely written in the early 20th century. This gripping narrative delves into the underworld of crime, following the harrowing escape of Chester Fay, a lifelong prisoner, and his desperate bid for freedom. The book explores themes of loyalty, morality, and the challenges faced by those trapped in a life of crime. In the story, Chester Fay escapes from Rockglen prison alongside an elderly convict, Charley O'Mara. After an intense breakout, their plans go awry, leading to Charley's fatal injury during a confrontation with guards. Before his death, Charley tasks Fay with looking after his daughter, Emily, who is living under the oppressive and dangerous management of a man named the Dropper. As Fay approaches Emily, he discovers her fear of her guardian and her life in the sordid environment of a Chicago dive. Determined to honor his promise to Charley, Fay confronts the Dropper in a fierce battle, ultimately rescuing Emily and planning a better future for her. The narrative showcases Fay's transformation from a criminal to a protector, intertwining action and emotion in a vivid exploration of human connection in the face of adversity. (This is an automatically generated summary.)
Release date is 2022-09-07
Roger Frank and Sue Clark
Keywords: Short stories; Orphans -- Fiction; Criminals -- Fiction; Escaped prisoners -- Fiction; Fay, Chester (Fictitious character) -- Fiction